Praktek Qadhi Nikah Tidak Tercatat Setelah Berlakunya Undang-Undang Perkawinan (Studi Penelitian di Wilayah Hukum Kota Sabang) - Fauzan Fauzan; Faisal Faisal; Hamdani Hamdani (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
Marriage is an bond between a man and a woman to justify the relationship as husband and wife. Illegal marriages or unregistered marriages still often occur in the practice of the people of Sabang City. This is due to the ease of managing the files. The purpose of this study is to explain and analyze the implementation of the practice of unregistered marriage qadhi as well as to explain and analyze the impact or legal consequences in the jurisdiction of the City of Sabang. This survey is a qualitative survey with a normative and empirical legal approach. The normative judicial approach examines laws and regulations related to unrecorded Gaddy marriage practices. While considering the normative provisions that can be applied in practice, an empirical legal approach provides an alternative solution to the problem of illegal marriage caddy practice in the jurisdiction of the people of the city of Sabang. The results of the study show that the practice of implementing qadhi marriages is not recorded in the view of Islamic law which has occurred for a long time and is still developing in the Sabang community due to the inability of the community to meet the requirements and mechanisms regulated by the Office of Religious Affairs (KUA). KUA does not want to take the risk to resolve the reasons related to unregistered marriage. Efforts that can be made are by marriage itsbat or remarriage. It is recommended to the public that marriages be carried out in accordance with written laws. Law enforcement officials should take firm action against the perpetrators of illegal/siri marriages so as to create a deterrent effect. For KUA, it should record and re-socialize couples who have unregistered marriages to be remarried so that they are legal according to regulations and religion.